2007
DOI: 10.1016/j.pepi.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the thermal and volatile evolution of Mars

Abstract: 14 15The thermal and volatile evolution of Mars has not been studied from the perspective of 16 consistency with the preservation of the Martian global dichotomy and estimates of the elastic 17 thickness over time. We use three thermal evolution models for Mars: 1) stagnant lid, 2) early 18 plate tectonics followed by stagnant lid, and 3) mantle overturn, to calculate the amount of 19 relaxation of the dichotomy boundary and elastic thickness values for Noachian-and Hesperian-20 aged terrains. To explore a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Therefore, although a dry mantle rheology cannot be ruled out, a wet mantle rheology is clearly preferred. These results are similar to those presented by Guest and Smrekar (2007) and Grott and Breuer (2008a), who also concluded that the low elastic thickness values in the Noachian are best compatible with wet crustal and mantle rheologies.…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, although a dry mantle rheology cannot be ruled out, a wet mantle rheology is clearly preferred. These results are similar to those presented by Guest and Smrekar (2007) and Grott and Breuer (2008a), who also concluded that the low elastic thickness values in the Noachian are best compatible with wet crustal and mantle rheologies.…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…Furthermore, the low elastic thickness values observed during the early Martian evolution are best compatible with a wet mantle rheology (Guest and Smrekar, 2007;Grott and Breuer, 2008a). However, to investigate the whole range of possible evolution scenarios, we will study wet as well as dry mantle rheologies.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…A wet lithospheric mantle rheology is consistent with the results based on comparative analyses between the evolution of effective elastic thickness through time and the thermal history models for Mars (Guest and Smrekar, 2007;Grott and Breuer, 2007). As the thickness of the crust in this region is ∼ 0-5 km thicker than the average planetary value , our results suggest an average thickness of ∼ 40-75 km for the Martian crust, which is consistent with the range of 38-62 km obtained by Wieczorek and Zuber (2004) from geophysical and geochemical arguments.…”
Section: Conclusion: Putting It All Togethersupporting
confidence: 81%
“…The use of a "standard" wet diabase for the Martian crust is consistent with extensive evidence for water-related geological activity during the Late Noachian and Early Hesperian (e.g., Head et al, 2001). Otherwise, a dry crustal rheology is hardly consistent with the comparison among the evolution of effective elastic thickness of the lithosphere and the thermal history models for Mars (Guest and Smrekar, 2007;Grott and Breuer, 2007).…”
Section: Heat Flow From the Depth Of Amenthes Rupes-related Thrust Faultmentioning
confidence: 80%